2021
DOI: 10.5435/jaaos-d-21-00151
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal Artery Entrapment Syndrome: A Diagnostic and Treatment Enigma for Orthopaedic Surgeons

Abstract: Popliteal artery entrapment syndrome (PAES) is an uncommon condition that causes recurrent posterior leg pain and foot paresthesia in running athletes. This condition occurs most commonly due to an accessory or abnormal implant of the medial head of the gastrocnemius muscle. It may mimic or coincide with other chronic conditions of the lower extremity including chronic exertional compartment syndrome but is most consistent with vascular claudication. Clinical features that distinguish PAES from other causes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A summary of the types of manuscripts included in this review is shown in Table 3. Noncomparative studies including opinion pieces/narrative reviews accounted for 45.4% of the included manuscripts [4, 6, 33–84], case reports (22%) [7, 85–109], and case series studies (17%) [110–129]. Five percent of the included manuscripts were systematic reviews [5, 130–134].…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the types of manuscripts included in this review is shown in Table 3. Noncomparative studies including opinion pieces/narrative reviews accounted for 45.4% of the included manuscripts [4, 6, 33–84], case reports (22%) [7, 85–109], and case series studies (17%) [110–129]. Five percent of the included manuscripts were systematic reviews [5, 130–134].…”
Section: Resultsmentioning
confidence: 99%